First Trimester Abortion and Psychiatric Morbidity - Aryal, Shreyashi; Basnet, Rachana Sharma (Journal of Nepal Health Research Council, 2024)
Background: Early pregnancy loss is a traumatic event following which clients may experience psychological morbidities. Mental illness is associated with multiple obstetric and social factors surrounding the period of pregnancy loss. The aim of this study was to find the prevalence of depression and anxiety before and after undergoing spontaneous or induced first trimester abortion and to analyze demographic and obstetric factors associated with it. Methods: This is an observational study conducted as Kathmandu Medical College (KMC) for a duration of one year from September 2022 to August 2023. All clients with abortion were screened for psychiatric morbidity using the The Hospital Anxiety and Depression Scale (HADS). Each client was assessed at first hospital visit and then at two weeks and two months following abortion. Level of anxiety and depression was analyzed in relation to socio-demographic factors and the type of abortion. Results: 171 clients with pregnancy loss were enrolled. Pre-abortion, severe anxiety was present in 6(13%) clients with spontaneous abortion. Pre-abortion, mild to severe anxiety was present in 31 (67.3%) clients and at two weeks and two months in 11 (23.9%) and 11 (23.9%) clients respectively. In clients undergoing induced abortion, varying levels of anxiety was present in 54(43.2%) pre-abortion, and 48(38.4%) and 54(43.2%) clients at two weeks and two months. Mild to moderate depression was seen in 21 (45.6%) among spontaneous abortion and 51 (40.8%) clients among induced abortion. Mean score on HADS decreased with time. Conclusions: Anxiety and depression were common following early pregnancy loss. Rate of anxiety seems to decrease with time in spontaneous abortion but in induced abortion it remains persistent. Rate of depression tends to decrease with time for both types of abortion. Keywords: Abortion; anxiety; depression; HADS; induced.